A tailored relocation stress intervention programme for family caregivers of patients transferred from a surgical intensive care unit to a general ward. Issue 5 (7th December 2016) - Lee, Seul; Oh, HyunSoo; Suh, YeonOk; Seo, WhaSook
Abstract : Aims and objectives: To develop and examine a relocation stress intervention programme tailored for the family caregivers of patients scheduled for transfer from a surgical intensive care unit to a general ward. Background: Family relocation stress syndrome has been reported to be similar to that exhibited by patients, and investigators have emphasised that nurses should make special efforts to relieve family relocation stress to maximise positive contributions to the well‐being of patients by family caregivers. Design: A nonequivalent control group, nonsynchronised pretest–post‐test design was adopted. Methods: The study subjects were 60 family caregivers of patients with neurosurgical or general surgical conditions in the surgical intensive care unit of a university hospital located in Incheon, South Korea. Relocation stress and family burden were evaluated at three times, that is before intervention, immediately after transfer and four to five days after transfer. Results: This relocation stress intervention programme was developed for the family caregivers based on disease characteristics and relocation‐related needs. In the experimental group, relocation stress levels significantly and continuously decreased after intervention, whereas in the control group, a slight nonsignificant trend was observed. Family burden levels in the control group increased significantly after transfer, whereas burden levels in the experimental group increased only marginally and nonsignificantly. No significant between‐group differences in relocation stress or family burden levels were observed after intervention. Conclusions: Relocation stress levels of family caregivers were significantly decreased after intervention in the experimental group, which indicates that the devised family relocation stress intervention programme effectively alleviated family relocation stress. Relevance to clinical practice: The devised intervention programme, which was tailored to disease characteristics and relocation‐related needs, may enhance the practicality and efficacy of relocation stress management and make meaningful contribution to the relief of family relocation stress, promote patient recovery and enhance the well‐being of patients and family caregivers.